2019
DOI: 10.1111/1750-3841.14702
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties and Digestion Characteristics of Corn Starch Esterfied by Malic Acid

Abstract: The objective of this study was to evaluate the effects of different degree of substitution on structural characteristics and crystalline properties of resistant starch esterfied by L‐malic acid. With the deepening of the esterification reaction, malate starches particles became larger, particle surface cracks and grooves increased which led to a decline in whiteness of malate starches. With the increase in the degree of substitution (DS), the initial phase transition temperatures (To) and endothermic enthalpi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Starch, as the main component of cereal grains and tubers, is one of the most abundantly available, inexpensive, and biodegradable polymers, commonly used in the food, pharmaceutical, textile, biomass energy, and chemical industries [1][2][3]. Furthermore, it is the most important source of metabolic energy in the human diet [4]. From a nutritional aspect, starch can be classified into three categories based on digestibility: rapidly digestible starch (RDS), slowly digestible starch (SDS), and resistant starch (RS) [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Starch, as the main component of cereal grains and tubers, is one of the most abundantly available, inexpensive, and biodegradable polymers, commonly used in the food, pharmaceutical, textile, biomass energy, and chemical industries [1][2][3]. Furthermore, it is the most important source of metabolic energy in the human diet [4]. From a nutritional aspect, starch can be classified into three categories based on digestibility: rapidly digestible starch (RDS), slowly digestible starch (SDS), and resistant starch (RS) [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…At present, different methods have been applied to prepare RS, including chemical, physical (hydrothermal), and enzymatic modification methods [10]. Among these techniques, the most effective way to increase the resistant starch content is through chemical modifications, such as carboxymethylation, esterification, and phosphorylation [4,5]. Recently, research on the reaction of starch and organic acids (citric, malic, lactic, acetic) in combination with heat-moisture treatment (HMT) as a means of manufacturing resistant starch in high yields has been increasingly favored [5,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, l-malic acid is easily prepared by microbial fermentation or enzymatic conversion which has stereospecificity, and can be used as a pasta enhancer (Battat et al, 1991;Iyyappan et al, 2019;Moon et al, 2008;Neufeid et al, 1991). In previous studies, physicochemical character of malate starch was studied (Tian et al, ,2016(Tian et al, , , 2019. In this study, the low degree of substitution malate starches were constructed by combining the chemical bonds of corn starch and l-malic acid, and the effects on physical and chemical properties, molecular characteristics, and digestion properties were studied to improve the processing characteristics of starch and improve product addition value to provide a theoretical basis for the development and utilization of malate starch.…”
mentioning
confidence: 99%
“…Recently, malic acid, a C4-dicarboxylic food-grade organic acid, has also become popular for the acid modification of starch. Tian et al (2019) successfully modified the digestion characteristics of corn starch using malic acid. Na et al (2021) reported the effect of malic acid treatment on various types of starch, determining that maize starch was the most effective substrate for increasing RS.…”
Section: Introductionmentioning
confidence: 99%